2012
DOI: 10.3126/nepjoph.v4i2.6537
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sutureless and glue free limbal conjunctival autograft for primary pterygium surgery

Abstract: Sutureless and glue free limbal conjunctival autografting following pterygium excision is a safe, effective and economical option for the management of primary pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
57
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 13 publications
14
57
1
Order By: Relevance
“…Many other reported series noticed even less displacement than the present study like Rathi G et al, 12 (2%), Kulthe SB et al 10 (3.7%) and D de Wit et al 14 (0%). A total percentage of graft stability noticed in the present series was 91.8%, which was similar to the observation done by Malik KPS et al (2012) 11 (87.5%), Rathi G et al 12 (98%) and Kulthe SB et al 10 (96.2%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Many other reported series noticed even less displacement than the present study like Rathi G et al, 12 (2%), Kulthe SB et al 10 (3.7%) and D de Wit et al 14 (0%). A total percentage of graft stability noticed in the present series was 91.8%, which was similar to the observation done by Malik KPS et al (2012) 11 (87.5%), Rathi G et al 12 (98%) and Kulthe SB et al 10 (96.2%).…”
Section: Discussionsupporting
confidence: 81%
“…10 The mean age of the patient in the study was 45.86 years. Malik KPS et al (2012) 11 and Rathi G et al (2015) 12 in their respective studies found mean age of the patients as 42.8 years and 42.5 years respectively. Rangu RV et al (2014) 8 also in their study on sutureless and glue-free conjunctival autograft reported the mean age of the patient to be 52.4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We promoted wound healing by primary intention through fixing the graft at scleral bed and wound edges this resulted in faster wound healing, less scarring and better cosmetic results. 12 carried out a study in 40 eyes with Primary nasal pterygium with suture less and glue free Limbal conjunctival autograft surgery followed by Bandaging for 48 hrs. and reported graft dehiscence in 2 Eyes (5%), graft retraction in 3 eyes (7.5%) and recurrence was seen in 1 eye (2.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The procedure is especially useful for closing large surgical defects following excision of extensive pterygium (Ang et al 2003). 3 Kenyon et al 9 first described a conjunctival autograft in 1985. They reported a recurrence rate of 5.3% and infrequent and relatively minor complications.…”
Section: History and Review Of Literaturementioning
confidence: 99%